Moderasi Beragama: Landasan Moderasi dalam Tradisi berbagai Agama dan Implementasi di Era Disrupsi Digital - Nisa, Muria Khusnun; Yani, Ahmad; Andika, Andika; Yunus, Eka Mulyo; Rahman, Yusuf (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the basis of moderation in the traditions of various religions and its implementation in the era of digital disruption. This study uses a qualitative approach and data processing using descriptive-analytical methods. The results and discussion of this study indicate that there are several foundations of moderation in all religious teachings. The teachings of religious moderation do not belong only to one particular religion, but to various religions even world civilizations also have that kind of teaching. This study concludes that religious moderation is indispensable in implementation in today's digital era. An important effort in implementing religious moderation today is aimed at creating a generation that is moderate and not easily influenced by radical ideas propagated from cyberspace. This study recommends the millennial generation and educational institutions to foster a sense of religious moderation in the midst of the era of digital disruption.